2014
DOI: 10.1371/journal.pone.0089740
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Study of Critical Patients with Hemorrhagic Fever with Renal Syndrome Complicated by Acute Respiratory Distress Syndrome

Abstract: ObjectivesThe aim of this study was to investigate the clinical characteristics and outcomes of critical patients with hemorrhagic fever with renal syndrome (HFRS) complicated by acute respiratory distress syndrome (ARDS).Materials and MethodsTo observe the demographic, epidemiological and clinical characteristics, and to explore the predictive effects for prognosis in laboratory findings, we conducted a detailed retrospective analysis of clinical records for critical patients with HFRS complicated by ARDS, tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
30
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(36 citation statements)
references
References 31 publications
6
30
0
Order By: Relevance
“…Our data of serum Cr and BUN in general supports the effects of the two compounds on the levels of serum UA. It has been reported that serum Cr levels are associated with renal dysfunction (Hoffmann et al, 2010;Adibelli et al, 2012;Du et al, 2014), and our data showed that smilaxchinosides A and C possessed potent activities in the reduction of hyperuricemia-induced renal dysfunction.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…Our data of serum Cr and BUN in general supports the effects of the two compounds on the levels of serum UA. It has been reported that serum Cr levels are associated with renal dysfunction (Hoffmann et al, 2010;Adibelli et al, 2012;Du et al, 2014), and our data showed that smilaxchinosides A and C possessed potent activities in the reduction of hyperuricemia-induced renal dysfunction.…”
Section: Discussionsupporting
confidence: 69%
“…Serum Cr and BUN levels can be associated with renal dysfunction. Renal damage can be accompanied by an increase in serum Cr and BUN indicating reduced urea and Cr clearance (Hoffmann et al, 2010;Adibelli et al, 2012;Du et al, 2014). Compared with the model group, the levels of serum Cr and BUN were suppressed significantly (both p < 0.01) by smilaxchinosides A and C. Moreover, smilaxchinosides A and C treatment at the dose of 10 mg/kg could significantly increase the renal UA handling parameter FEUA (both p < 0.05) and can enhance UA excretion.…”
Section: Discussionmentioning
confidence: 99%
“…Hemorrhagic fever with renal syndrome (HFRS) is a rodent-borne disease that is caused by Hantavirus (HV), with major clinical characteristics of fever, hemorrhage, hypotension, and renal damage [ 1 , 2 ]. The typical disease progresses through five phases: febrile, hypotensive, oliguric, diuretic, and convalescent [ 3 , 4 ]. China is the most severe endemic area of HFRS in the world, with a high incidence rate in the last ten years [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…HFRS is endemic in all 33 provinces of the People's Republic of China, where it is a significant public health problem, in which 20,000–50,000 human cases are diagnosed annually [3] . Notably, Xi'an city, which is the central district of the Shaanxi province, had an increasing HFRS incidence and mortality rate due to HFRS over the last three years [4] . There are five successive clinical phases in typical HFRS patients.…”
Section: Introductionmentioning
confidence: 99%